Love that Binds: An Ecospiritual Reading of Rumi’s Poetry - Saddam, Widad Allawi; Abbas, Zainab Ibrahim (Al-Adab Journal, 2020)
Rumi is endorsed for being one of the most famous Persian Sufi poets. He is considered a poet of love for all creation. In his poetry, one finds a close admiration of natural world that comes from love and results in even a greater love for the creator of the natural forces. This study aims to analyze selected poems of Rumi to inspect his views on environment and nature knitted closely with love and spirituality. Ecospirituality, a rather new approach to inspect the relationship of the environment and literary works from a spiritual point of view was employed to comment on Rumi’s dealing with creation and love for God in his poetry.